In Search of Optimal Cell Components for Polyoxometalate-Based Redox Flow Batteries: Effect of the Membrane on Cell Performance - Ángela Barros; Jacobus C. Duburg; Lorenz Gubler; Estibaliz Aranzabe; Beñat Artetxe; Juan Manuel Gutiérrez-Zorrilla; Unai Eletxigerra (Energies)
Redox Flow Batteries (RFBs) are promising large-scale Energy Storage Systems, which support the integration of renewable energies into the current electric grid. Emerging chemistries for electrolytes, such as Polyoxometalates (POMs), are being studied. POMs have attracted great interest because of their reversible multi-electron transfers and the possibility of tuning their electrochemical properties. Recently, the cobalt-containing Keggin-type species [CoW12O40]6− (CoW12) has been successfully implemented in a symmetric RFB, and its further implementation calls for new materials for the membrane to enhance its cell performance. In this work, different types of ion exchange membranes (Nafion™-NR212, FAPQ-330 and Amphion™) were tested. The electrolyte uptake, swelling, conductivity and permeability of the membranes in the CoW12 electrolyte, as well as a detailed cell performance study, are reported herein. Better performance results ascribed to the robustness, efficiency and energy density of the system were found for Nafion™-NR212, with 88.5% energy efficiency, 98.9% capacity retention and 3.1 Wh L−1 over 100 cycles at 20 mA cm−2. FAPQ-330 and Amphion membranes showed large capacity fade (up to 0.2%/cycle). Crossover and the low conductivity of these membranes in the mild pH conditions of the electrolyte were revealed to be responsible for the reduced cell performance.